The room with the second-best view [large type] - Smith, Virginia, 1960- (Smith, Virginia, 1960- Tales from the Goose Creek B & B., 2017)
Excitement is in the air in Goose Creek, Kentucky, as the small town prepares to celebrate its 150th anniversary and the veterinarian's upcoming wedding. But trouble is brewing in this provincial paradise... Al Richardson agreed to open a B&B with his wife after his retirement in two years, but Millie secretly invites some guests to stay for the wedding. She plans to be the most gracious Southern hostess until a tumble down the stairs leaves her unprepared for their quirky and cantankerous first guest. Meanwhile, the town's anniversary plans are in a state of chaos as the celebration committee scrambles to raise the necessary funds an effort spearheaded by a "newcomer," which ruffles the townsfolk's feathers. Goose Creek has lasted 150 years. Can it survive the next month? "